2011
DOI: 10.1042/bj20100884
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an inhibitory fibroblast growth factor receptor 2 (FGFR2) molecule, up-regulated in an Apert Syndrome mouse model

Abstract: AS (Apert syndrome) is a congenital disease composed of skeletal, visceral and neural abnormalities, caused by dominant-acting mutations in FGFR2 [FGF (fibroblast growth factor) receptor 2]. Multiple FGFR2 splice variants are generated through alternative splicing, including PTC (premature termination codon)-containing transcripts that are normally eliminated via the NMD (nonsense-mediated decay) pathway. We have discovered that a soluble truncated FGFR2 molecule encoded by a PTC-containing transcript is up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…59 These mutations are thought to result in sustained FGFR2 signaling due to increased affinity of the ligand to the receptor in the absence of sustained FGF2 expression. 60,61 Although the effects of these changes have been studied in bone formation, little is known about the effects on the EOMs specifically. It is important to note that an examination of fetal orbital tissues showed that the EOMs specifically express FGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…59 These mutations are thought to result in sustained FGFR2 signaling due to increased affinity of the ligand to the receptor in the absence of sustained FGF2 expression. 60,61 Although the effects of these changes have been studied in bone formation, little is known about the effects on the EOMs specifically. It is important to note that an examination of fetal orbital tissues showed that the EOMs specifically express FGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, soluble FGFR1s were mapped and found to be the two and three Ig-like domain isoforms of FGFR1 IIIc and a carboxyl-terminal cleavage peptide from the two and three Ig-like domain isoforms of FGFR1IIIb. Secreted receptors truncated after either IgI or IgIII by the introduction of early stop or premature termination codons have also been identified in other studies (Johnson and Williams, 1993;Wheldon et al, 2011). For example, a secreted receptor, FGFR1IIIa, is the IIIa splice form that contains intronic sequence upstream of exons 8 and 9, terminating within the IgIII domain and with no known signaling ability .…”
Section: Soluble Receptorsmentioning
confidence: 97%
“…The deletion described here removes the entire intron between exons IIIb and IIIc, and therefore all known regulatory elements within this intron, as well as an ESS from each exon. It is difficult to predict exactly how the chimeric exon would be processed in vivo , but the AS phenotype of the child, which implies a gain-of-function mechanism, does indicate that production of FGFR2 containing the in-frame chimeric exon is likely to occur in critical target tissues; by contrast, skipping of both exons IIIb and IIIc would generate an isoform with loss-of-function properties [22]. …”
Section: Discussionmentioning
confidence: 99%